Dante intermédial : une introduction - Caroline Fischer (Between, 2020)
Expressions like ‘intermedial Dante’, ‘Dante and intermediality’ or ‘Dante’s reception across media’ open up a field so immensely vast that one cannot even begin to describe it within the limits of a journal article. The notes that follow attempt to provide a point of departure for those who are just approaching the study of Dante’s intermedial reception.